Uji Klasifikasi Yudisial dalam Pembunuhan terhadap Gender: Honor Killing dan Intimate Partner Femicide - Zul Khaidir Kadir (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Criminal responsibility is constructed through the elements of homicide offences, the assessment of mens rea, accomplice liability, and sentencing rationality grounded in individual culpability. In judicial practice, however, cases involving the killing of women are frequently framed at the outset through the labels of “honour” or “intimate relationship,” leading honour killing and intimate partner femicide to be treated as interchangeable categories. This practice shifts the assessment of intent toward the perpetrator’s narrated motive and narrows accountability to the last physical actor. This research aims to formulate, first, legal criteria and evidentiary indicators for distinguishing the two categories through a staged judicial classification test, and second, to assess the implications of such classification for the construction of intent, the attribution of responsibility to non-executing actors, and sentencing rationality through disciplined reason-giving. The study employs a normative legal method with a conceptual approach, based on library research of primary and secondary legal materials. The findings demonstrate that the core deficiency lies in the absence of an operational classification device, allowing honour narratives to displace structured mens rea analysis and to obscure the causal contributions of non-executors. The article proposes working definitions and a stepwise indicator-based test—focusing on the presence of determinative social pressure or sanctioning, provable role allocation within perpetrator networks, and prior threats framed in terms of honour restoration—and links these indicators to concrete doctrinal consequences for intent, accomplice liability, and sentencing. Through this framework, judicial reasoning is redirected from label-driven interpretation toward accountability, while restraining the use of honour as a mitigating rationale and preventing femicide patterns from being concealed by reputational narratives.